Strangulated Left Lateral Inguinal Hernia in a 54-Year-Old Woman: A Case Report - Sudirman, Taufik; Surya, Clarissa; Marina, Sinta (Medicinus, 2023)
Introduction: Around 20 millions of hernia repairs were done annually with women presenting least cases. The occurrence of inguinal hernia in female patients is 3-6%, which is lower than men (27-43%). Inguinal hernia itself may present as a bulge in the groin in which the definitive treatment is through surgery. Although many research were done for hernia repair in men, guidelines for women are still currently observed with less favourable outcomes.Case illustration: A 54-year-old woman came to the ED complaining of pain of protruding bulge in the groin area for two hours. The patient has had a history of bulging for three years, which was previously reducible. Examination of the inguinal region revealed a lump with a diameter of +/- 4 cm and painful when palpated. Abdominal USG showed a left inguinal hernia consisting intestinal tissues. Open herniotomy with mesh grafting was performed and the patient got discharged after 4 days of hospitalisation.Conclusion: Lifetime risk for development of inguinal hernia is higher in men compared to women, but the rate of emergency procedures in women is 3 to 4-fold higher than in men. Guidelines for hernia repair in women show less favourable results than in men. Therefore, special steps must be taken in the repair of inguinal hernia in women.